2015
DOI: 10.1371/journal.pone.0140801
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern and Climate Preferences of the Representatives of the Cosmopolitan Genus Sirthenea Spinola, 1840 (Heteroptera: Reduviidae: Peiratinae)

Abstract: The main goal of this study was to predict, through the use of GIS tool as ecological niche modelling, potentially suitable ecological niche and defining the conditions of such niche for the representatives of the cosmopolitan genus Sirthenea. Among all known genera of the subfamily Peiratinae, only Sirthenea occurs on almost all continents and zoogeographical regions. Our research was based on 521 unique occurrence localities and a set of environmental variables covering the whole world. Based on occurrence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Therefore, Sirthenea is of considerable interest as a potential model group for a wide range of studies spanning several fields such as evolutionary biology, systematics, biogeography and ecology. Our previous study showed that representatives of Sirthenea are ground-dwelling, non-specialized predators that prey on other insects on the ground in microhabitats that are mainly located in low-lying areas in tropical and temperate climates (Chłond & Bugaj-Nawrocka, 2015), which is consistent with the observations of other authors (Willemse, 1985). During the almost two centuries since the description of the first Sirthenea species as Reduvius carinatus by Spinola in 1837, the number of known species has increased to 41 (Maldonado Capriles, 1990; Cai & Tomokuni, 2004; Chłond, 2008a, 2008b), which was largely due to the high degree of variability associated with the wide distribution of selected species.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, Sirthenea is of considerable interest as a potential model group for a wide range of studies spanning several fields such as evolutionary biology, systematics, biogeography and ecology. Our previous study showed that representatives of Sirthenea are ground-dwelling, non-specialized predators that prey on other insects on the ground in microhabitats that are mainly located in low-lying areas in tropical and temperate climates (Chłond & Bugaj-Nawrocka, 2015), which is consistent with the observations of other authors (Willemse, 1985). During the almost two centuries since the description of the first Sirthenea species as Reduvius carinatus by Spinola in 1837, the number of known species has increased to 41 (Maldonado Capriles, 1990; Cai & Tomokuni, 2004; Chłond, 2008a, 2008b), which was largely due to the high degree of variability associated with the wide distribution of selected species.…”
Section: Introductionsupporting
confidence: 91%
“…Our results provide a hypothesis for understanding the evolutionary history of the genus, which is supported by the evolution of the ecological niches that are occupied by representatives of Sirthenea (Couvreur & Baker, 2013; Chłond & Bugaj-Nawrocka, 2015). Moreover, all of the information that was obtained during previous studies (Chłond & Bugaj-Nawrocka, 2015; Chłond, Bugaj-Nawrocka & Sawka-Gądek, 2017; Chłond, 2018) combined with the currently obtained data, which can be linked to geological time, not only provide valuable insight into the evolutionary history of the Sirthenea , but also allow for understanding the diversity (27 species) of this cosmopolitan genus. In this study, we aimed to investigate the phylogenetic relationships of Sirthenea based on morphological and molecular data, and to estimate the divergence times within all of the known species of Sirthenea .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This species has a very broad distribution that covers the southern part of western, central and eastern Asia. Our previous studies clearly show a very wide spectrum of ecological niches occupied by this genus (Chłond & Bugaj‐Nawrocka ); however, S. flavipes drew our attention because of the broad range of ecological niches occupied by it compared with congeners. Moreover, we have observed a high degree of polymorphism among individuals within this species (mainly body colouration and size), which show a characteristic gradient across its entire distributional range.…”
Section: Introductionmentioning
confidence: 97%
“…The genus Sirthenea , described by Spinola (), is one of the largest genera in the subfamily Peiratinae with 40 described species (Willemse ; Sucheta Chopra ; Cai & Lu ; Maldonado ; Murugan & Livingstone ; Lee & Kerzhner ; Cai & Tomokuni ; Chłond , b). Representatives of Sirthenea are ground‐dwelling, non‐specialised predators, preying on other insects at night on the ground and in very diverse microhabitats (Chłond & Bugaj‐Nawrocka ). This genus can be easily recognised among other genera of Peiratinae by its distinctly elongated body and anteocular part of its head, shortened and rounded femora and the absence of fossa spongiosa on the mid tibiae (except in the Australian species S. laevicollis Horváth, ).…”
Section: Introductionmentioning
confidence: 99%